Ralph Waldo Emerson versus Cormac McCarthy: The Annihilation of Emerson’s Values in McCarthy’s The Road - Kestermann, Nora (Current Objectives of Postgraduate American Studies, 2012)
Focusing on the significant and also ambivalent role that nature has always played in American literature and culture, the article examines the striking contrast between Emerson’s description of nature in his essay “Nature“ (1836) and McCarthy’s approach to the same subject in his novel The“ Road“ (2006). The aim of the article is to reveal the presence of a subtext in which McCarthy hints at the alienation between humans and the natural environment and thus puts forth a radical disillusionment with Emersonian values. Whereas transcendentalists come to read nature as a medium to find spirituality and to be able to communicate with the divine, McCarthy projects confusion and disorder through (human) terror onto nature—or rather what is left of it in the darkened and almost entirely destroyed world in The Road“. Against the background of a journey through a burned-out America which is usually celebrated for its natural beauty, the protagonists have to face a desolate waste land: ‘Nature’s Nation’ has turned into a stifling landscape of degeneration. The article examines how the idealistic concept of American nature with which the country once strove to identify itself is exposed, rejected and in fact, heavily attacked in The Road“.